Northern Mindanao State Institute of Science and Technology 8600 Ampayon, Butuan City, Philippines - EMILIO .O ANINO (SEAMEO BIOTROP, 2000)
Selected fungicides were tested to control damping-off affecting bagrasÂ seedlings in the Central Nursery of the Paper Industries Corporation of the Philippines (PICOP), Surigao del Sur, Philippines. The fungicides, at three concentrations each, were applied once before seed sowing to control pre-emergence damping-off and applied again after germination to control post-emergence damping-off. Ajax detergent (2g/l H2O), Benlate (0.5 g/1 H2O), Brassicol (1.5 gv'l H2O), and Fungitox (1.0 g/1 H2O) provided the best level of control against the disease. Ajax detergent is the most practical among the best chemicals because it is cheap, locally available, not a health hazard, and less polluting. Key Words :Â Eucalyptus deglupta/ Seeds/Nursery/flWzoctoma so/am'/Fungicides/Application